Physical Education Facilities and Infrastructure at Elementary Schools DABIN III Kersana District Brebes Regency - Tatang Suryadin; Indra prabowo; M. Reza Adriansyah (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The background in this study is that the availability and condition of physical education facilities and infrastructure in public elementary schools throughout Dabin III, Kersana District, Brebes Regency is unknown. This study aims to determine the availability and condition of physical education facilities and infrastructure in public elementary schools throughout Dabin III, Kersana District, Brebes Regency based on the standards of Permendiknas No. 24 of 2007. This research is a quantitative descriptive study using a survey method. Data collection techniques using observation sheets. The population in this study were public elementary schools throughout Dabin III, Kersana District, Brebes Regency, which amounted to 12 schools. The sample in this study were all schools in Dabin III, Kersana District, Brebes Regency because this study was a population study. The data analysis technique used in this research is descriptive percentage. The results showed that the level of availability of physical education facilities and infrastructure in public elementary schools throughout Dabin III, Kersana District, Brebes Regency, was on average 28.96%. Meanwhile, for the condition of physical education facilities and infrastructure that are available in good condition in public elementary schools throughout Dabin III, Kersana District, Brebes Regency, the average is 86.67%. Suggestions for schools or related agencies in order to determine the next step so that the problem of the availability of physical education facilities and infrastructure that is still lacking can be quickly resolved.